Development of Corrosion-Erosion Test Equipment in CO2 Environment and Study of The Effect of Partial Pressure of CO2 on Corrosion-Erosion Rate of API 5L X65 and API 5L X60 Steel in Acetic Acid Environment - Arif Hidayat, Muhammad
Corrosion due to CO2 and organic acid is the common problem of the transport system in oil and gas industries. In addition, fluid flow in the pipeline can also exacerbate damage caused by corrosion accompanied by erosion. In this environment, material selection must be right to get maximum benefit. In this research, we study about the effect of CO2 partial pressure on corrosion-erosion rate on API 5L X65 and API 5L X60 steel pipe material in the acetic acid environment accompanied by fluid flow. Research is started by developing a corrosion testing equipment. The tests were carried out by immersion method (168 hours) in 3360 ppm acetic acid solution with 850 rpm fluid flow at 2 bar and 5 bar CO2 pressure. Characterization carried out in the form of visual observations, stereo microscopes, changes in weight, and corrosion rate. The test results show that the corrosion rate of API 5L X65 steel at 5 bars is 0.62 times lower than 2 bars. Corrosion rate of API 5L X60 steel at 5 bars is 1.16 times higher than 2 bars. Corrosion rate of API 5L X65 steel is 1.65 times higher than API 5L X60 steel at 2 bars pressure. Corrosion rate of API 5L X65 steel is 0.45 times lower than that of API 5L X60 steel at 5 bars pressure.